Comparison of Antioxidant Activity of Ethanol Extract of Fruit and Okra Leaves (Abelmoschus esculentus L. Moench) with DPPH and ABTS Methods - Hendri Faisal; Handayani, Sri (Indonesian Journal of Pharmaceutical and Clinical Research, 2019)
Excessive free radical activity in the human body can be characterized by pathological conditions such as cardiovascular disease, pre-natal complications, arthritis, cataracts, parkinsonism, alzheimer's, and aging. One way to prevent the formation of free radicals is to use nutrients that act as antioxidants. Natural antioxidants found in fruits and vegetables are effective free radicals and are considered non-toxic when compared with synthetic antioxidants, one of which is the okra plant Abelmoschus esculentus L.The purpose of this study is to determine differences in the antioxidant activity ethanol extract of fruit and okra leaves with DPPH method and ABTS method. The method used in this study is the maceration extraction method with 70% ethanol solvent to obtain fruit extracts and okra leaves. The antioxidant activity test was carried out by the DPPH (1,1-diphenyl-2-picrylhydrazi) method by measuring the absorption of a mixture of sample extracts and DPPH by UV-Visible spectrophotometry at a wavelength of 520 nm and by the ABTS method ((2,2-azinobis- (3 -Ethylbenzothiazoline-6-Sulfonic Acid) by measuring the absorption of a mixture of sample extracts and ABTS by UV-Visible spectrophotometry at a wavelength of 734 nm. measurement of antioxidant activity of okra fruit ethanol extract by ABTS method has very strong antioxidant activity (IC50 24.50 ppm)